ОЦІНКА РЕЗУЛЬТАТІВ СПОЛУЧЕННЯ РИНКІВ ЕЛЕКТРИЧНОЇ ЕНЕРГІЇ НА РИНКУ «НА ДОБУ НАПЕРЕД» - Парус, Є.В.; Євдокімов, В.А. (Інститут електродинаміки НАН України, Київ, 2024)
The publication is devoted to the method of preliminary analysis of the results of the electricity market coupling in the "day-ahead" market segment. The relevance of the task of developing methods for preliminary evaluation of the results of the coupling of the "day-ahead" market of Ukraine with European interstate electricity exchanges is substantiated. The theoretical basis for the procedure for the selection of a separate external factor, with the aim of numerically evaluating the influence of such a factor that affects the change in the market equilibrium, is presented. The main components of the mathematical apparatus for finding market equilibrium in coupled electricity markets with the use of net export functions are described. The foundations for building algorithms for finding optimal solutions are determined. Features of the application of the proposed method on the example of the analysis of the results of Ukraine and Moldova electricity market coupling are demonstrated. Approaches to the creation of the function of Moldova's net export are shown, taking into account that the current structure of the Moldovan electricity market does not provide for the operation of the " day ahead"  market segment. An example of simulation modeling of the processes of Ukraine and Moldova electricity market coupling for two typical hours is given. An example of the analysis of simulation results and preliminary conclusions regarding the consequences of Ukraine and Moldova electricity market coupling is shown. References 20, figures 3.